COMPREHENSIVE ANALYSIS OF PROMOTING HOLISTIC PATIENT CARE THROUGH COLLABORATIVE PRACTICES AMONG SOCIAL WORKERS, NURSES, AND PHARMACISTS - SADDAM HUSSAIN ABUSAQ, GHAZI HUSSAIN ALI ABUSAQ, HAMAD MAHDI SALEM ALYAMI, ALI HAMAD AL RAKAH ALYAMI, MOHAMMED SHAEEL SEDRAN, HUSSAIN MUSLIH N ALYAMI, IBRAHEEM MOHAMMED ALSALEM (Chelonian Research Foundation, 2023)
In the modern healthcare system, holistic patient care is now a crucial aspect of healthcare meant to comprehensively cater to patients' requirements. The synergism among healthcare professionals, such as social workers, nurses, and pharmacists, cannot be overestimated, as it is the primary engine behind all-encompassing healthcare that not only focuses on physical well-being but also incorporates the psychosocial and pharmaceutical spheres to ensure overall patient welfare. This paper aims to describe the collaborative processes and team efforts among these three healthcare professionals to ensure holistic patient care. It identifies the contributions of social workers, nurses, and pharmacists in the management of patient care and further details the benefits associated with interdisciplinary collaborations as well as the various strategies for implementation. By helping shape a multidisciplinary approach, healthcare systems can make use of their potential to the maximum and achieve better outcomes for patients and a higher quality of care delivery. Keywords: Integrated care, healthcare sector, the social workers and nurses, complex tasks,